Multiple non syndromic supernumerary teeth in permanent dentition. A case report - Aparcana-Quijandría, Pedro Martin Jesús (2021)
The number of teeth can be increased by extra teeth named Supernumerary Teeth (ST). Multiple ST or hyperdontia is consider when there are five or ST with non syndromic association, which is a dental anomaly with a prevalence less than 1% of the reports of this alteration. The aim of this report was to keep record an unusual case of non- syndromic supernumerary teeth in a permanent dentition patient. Intraoral examination of a 22 years old woman revealed permanent dentition with presence of two supernumerary teeth in the upper central region, one of them palatally to 1.2, and another distal to 3.5. Radiographic findings: A panoramic radiograph showed us impacted supernumerary teeth between 1.5 and 1.4, another in similar condition, 1.1 in horizontal position, agenesy of 2.2 tooth, and two supernumeraries more between right lower bicuspids. The early diagnosis of ST is essential to avoid future alterations caused by this dental anomaly; as well as an adequate examination that allows to rule out the association with hyperdoncia related to some syndrome.